Both high and low plasma levels of 25-hydroxy vitamin D increase blood pressure in a normal rat model. Issue 11 (14th December 2016) - Mirhosseini, Naghmeh Z.; Knaus, Steven J.; Bohaychuk, Kaylee; Singh, Jaswant; Vatanparast, Hassan A.; Weber, Lynn P.
Abstract: The lower threshold plasma 25-hydroxy vitamin D (25(OH)D) level for optimal cardiovascular health is unclear, whereas the toxicity threshold is less clear. The aim of this study was to examine the cardiovascular–vitamin D dose–response curve in a normal rat model. Doses of cholecalciferol ranged from deficiency to toxic levels (equivalent to human doses of 0, 0·015, 0·25 and 3·75mg/d) for 4 weeks, and then cardiovascular health was examined using blood pressure telemetry and high-resolution ultrasound in normal male rats ( n 16/group, 64 rats total). After 1 month, only the 0·25mg/d group had plasma 25(OH)D that was within current recommended range (100–125 nmol/l), and all groups failed to change plasma Ca or phosphate. Systolic blood pressure increased significantly (10–15 mmHg) in the rat groups with plasma 25(OH)D levels at both 30 and 561 nmol/l (groups fed 0 and 3·75mg/d) compared with the group fed the equivalent to 0·015mg/d (43 nmol/l 25(OH)D). Although not significant, the group fed the equivalent to 0·25mg/d (108 nmol/l 25(OH)D) also showed a 10 mmHg increase in systolic blood pressure. Carotid artery diameter was significantly smaller and wall thickness was larger, leading to higher peak carotid systolic blood velocity in these two groups. Despite these vascular changes, cardiac function did not differ among treatment groups. The key finding in this study is that arterial stiffness and systolic blood pressure both showed a U-shaped dose–response for vitamin D, with lowest values (best cardiovascular health) observed when plasma 25(OH)D levels were 43 nmol/l in normal male rats.